AN INTEGRATED FRAMEWORK FOR CONTROL VALVE STICTION DETECTION AND SEVERITY QUANTIFICATION USING BUTTERFLY SHAPE-BASED METHOD - KAMARUDDIN, BASHARIAH (2021)
Control valves are found throughout industrial process plants as the final control element in control loops